ESTUDIO SOBRE EL JUEGO EN EL AULA: PROPUESTA PARA MEJORAR LA ENSEÑANZA DE LAS CIENCIAS SOCIALES EN EDUCACIÓN PRIMARIA - Evelio José García González; Francisco Javier Hinojo Lucena (European Scientific Journal, ESJ, 2015)
INTRODUCTION. Teachers frequently find a lot of difficulties when it comes to teaching Social Sciences at Primary School due to its contents. So, pupils’ motivation tends to be very low in most cases. When pupils come across new challenges derived from the subject, they may pay less attention and they might not study as a consequence. Everybody knows that children love playing; regardless of the type of game it is proposed. In consequence, games will be implemented in the classroom in order to test the role that games can play in pupils’ motivation. METHOD. To begin with, some Primary School teachers have been interviewed to know what they think about using games in the Social Sciences classroom. Next, pupils’ behaviour and their degree of commitment have been registered in some classrooms where games have not been used as a teaching technique. After that, some games related to the contents of the subject have been designed and later implemented in the classroom. Then, pupils’ behaviour and their degree of commitment have been registered in those classrooms where games have been implemented. Finally, results have been compared, paying special attention to conflictive students. RESULTS. It must be noted that pupils’ motivation grows dramatically in those sessions where games have been used. Furthermore, the disturbance of the normal rhythm in class by those students considered as conflictive is considerably diminished. DISCUSSION. Traditional methodologies are still used in Social Sciences teaching despite pupils’ motivation improvement when games are implemented as a teaching technique.